2002
DOI: 10.1007/s00432-002-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuclear localization of transcription factor YB-1 in acquired cisplatin-resistant ovarian cancer

Abstract: The expression of YB-1 in the nucleus seems to be associated with acquired cisplatin resistance in ovarian cancers. Nuclear YB-1 might be a useful predictive marker indicating cisplatin sensitivity and/or a target molecule to treat recurring ovarian cancers by cisplatin-based second-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 8 publications
2
60
0
Order By: Relevance
“…Our observations in clinical samples support the hypothesis that nuclear translocation of YB-1 is involved in the up-regulation of P-glycoprotein in breast cancers, both in those untreated and treated with anticancer drugs. In ovarian cancer, alteration of negative nuclear YB-1 expression in primary lesions to positive nuclear YB-1 expression in recurrent lesions was detected in f30% of tumors treated with regimens containing cisplatin, suggesting that nuclear YB-1 plays an important role in acquired cisplatin resistance in ovarian cancer (22). In the present study, the patients with breast cancer that showed translocation of YB-1 from the cytoplasm to the nucleus showed a significantly reduced response to paclitaxel.…”
Section: Discussionsupporting
confidence: 44%
“…Our observations in clinical samples support the hypothesis that nuclear translocation of YB-1 is involved in the up-regulation of P-glycoprotein in breast cancers, both in those untreated and treated with anticancer drugs. In ovarian cancer, alteration of negative nuclear YB-1 expression in primary lesions to positive nuclear YB-1 expression in recurrent lesions was detected in f30% of tumors treated with regimens containing cisplatin, suggesting that nuclear YB-1 plays an important role in acquired cisplatin resistance in ovarian cancer (22). In the present study, the patients with breast cancer that showed translocation of YB-1 from the cytoplasm to the nucleus showed a significantly reduced response to paclitaxel.…”
Section: Discussionsupporting
confidence: 44%
“…In other tumors like ovarian, breast, colon and lung cancers it has been described that YB-1 is frequently overexpressed and shows increased nuclear localization. 29,[31][32][33][34] Nuclear localization of YB-1 correlates with tumor progression and a poor prognosis in tumor patients. 31,32,34 Furthermore, translocation of YB-1 to the nucleus can be achieved by UV irradiation, anticancer agents, hyperthermia, phosphorylation, or association with p53 or splicing factor SRp30c.…”
Section: Discussionmentioning
confidence: 99%
“…29,[31][32][33][34] Nuclear localization of YB-1 correlates with tumor progression and a poor prognosis in tumor patients. 31,32,34 Furthermore, translocation of YB-1 to the nucleus can be achieved by UV irradiation, anticancer agents, hyperthermia, phosphorylation, or association with p53 or splicing factor SRp30c. 13,35,36 The nuclear translocation of YB-1 seen in tumor cells might indicate that the function as a transcriptional regulator preponderates the function as a cytoplasmic mRNA-binding protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When human cancer cells are treated with ultraviolet (UV) irradiation or anticancer agents, YB-1 translocates into the nucleus [10]. For ovarian cancer it has been shown that nuclear expression of YB-1 is associated with an acquired cisplatin resistance [11]. Transfection of human epidermoid cancer cells with a YB-1-antisense construct resulted in increased sensitivity to cisplatin, mitomycin C and UV radiation, which suggests a protective effect of YB-1 against cytotoxic effects of agents that induce cross-linking of deoxyribonucleic acid (DNA) [12].…”
mentioning
confidence: 99%